Recent advances in biomechanics (IntechOpen, 2020)
This book presents an understanding of biomechanics through chapters analyzing human behavior in sport from a medical perspective. It offers a comprehensive range of principles, methods, techniques, and tools to provide the reader with clear knowledge of the impact of biomechanic processes. The text considers physical, mechanical, and biomechanical aspects and is illustrated by different key application domains such as sports performance, sports science, ergonomy science, gait and human posture, and musculoskeletal disorders in medicine. The first three chapters provide useful tools for measuring, generating, simulating, and processing in biomechanics with the clinical and experimental applications in medicine. The last section describes the application of biomechanics in sport performance. Engineers, researchers, and students from biomedical engineering and health sciences, as well as industrial professionals, can profit from this compendium of knowledge on biomechanics applied to the human body.